Implementation of the trauma registry as a tool for quality improvement in trauma care in a brazilian hospital: the first 12 months - PARREIRA,JOSÉ GUSTAVO (2015)
ABSTRACTObjective:to analyze the implementation of a trauma registry in a university teaching hospital delivering care under the unified health system (SUS), and its ability to identify points for improvement in the quality of care provided.Methods:the data collection group comprised students from medicine and nursing courses who were holders of FAPESP scholarships (technical training 1) or otherwise, overseen by the coordinators of the project. The itreg (ECO Sistemas-RJ/SBAIT) software was used as the database tool. Several quality "filters" were proposed to select those cases for review in the quality control process.Results:data for 1344 trauma patients were input to the itreg database between March and November 2014. Around 87.0% of cases were blunt trauma patients, 59.6% had RTS>7.0 and 67% ISS<9. Full records were available for 292 cases, which were selected for review in the quality program. The auditing filters most frequently registered were laparotomy four hours after admission and drainage of acute subdural hematomas four hours after admission. Several points for improvement were flagged, such as control of overtriage of patients, the need to reduce the number of negative imaging exams, the development of protocols for achieving central venous access, and management of major TBI.Conclusion: the trauma registry provides a clear picture of the points to be improved in trauma patient care, however, there are specific peculiarities for implementing this tool in the Brazilian milieu.